2010
DOI: 10.1007/s10706-010-9333-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Soils and Laboratory Simulated Electrolyte Solution

Abstract: To study the impact of salt water intrusion on two types of soils from west coast region of India were investigated in the laboratory. The key characteristics evaluated included Atterberg limits, compaction characteristics, hydraulic conductivity and chemical characteristics of selected soils. The sea at this coast receives effluent from different points and hence the characteristics change with time and locality. Therefore, to maintain uniform composition, 0.5 N sodium chloride solution (NaCl) was prepared in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Hydraulic conductivity values of GCLs are found to be less than 6 Â 10 À11 m/s up to ionic strength up to 100 mM, while for solutions with ionic strength !500 mM to NH 4 þ they range from 1.6 Â 10 À6 to 5.2 Â 10 À6 m/s found (Setz et al 2017). Similar results showing that hydraulic conductivity increases with increasing ion concentration have also been revealed by other researchers (Shackelford et al 2000;Jo et al 2004;Mishra et al 2009;Nayak et al 2010;Oren & Demirkiran 2015).…”
Section: Salt Solutionssupporting
confidence: 80%
See 1 more Smart Citation
“…Hydraulic conductivity values of GCLs are found to be less than 6 Â 10 À11 m/s up to ionic strength up to 100 mM, while for solutions with ionic strength !500 mM to NH 4 þ they range from 1.6 Â 10 À6 to 5.2 Â 10 À6 m/s found (Setz et al 2017). Similar results showing that hydraulic conductivity increases with increasing ion concentration have also been revealed by other researchers (Shackelford et al 2000;Jo et al 2004;Mishra et al 2009;Nayak et al 2010;Oren & Demirkiran 2015).…”
Section: Salt Solutionssupporting
confidence: 80%
“…Researchers mainly addressed two issues when examining the effect of salt solutions on the hydraulic conductivity of CCLs and GCLs. In the studies, the effect of ion concentration on hydraulic conductivity (Shackelford et al 2000;Jo et al 2004;Yilmaz et al 2008;Mishra et al 2009;Nayak et al 2010;Oren & Demirkiran 2015;Setz et al 2017;Wang et al 2019) and the effect of increases in cation valence on hydraulic conductivity (Jo et al 2004;Mishra et al 2009;Shariatmadari et al 2011;Xue et al 2012;Chen et al 2019) were investigated. In Table 2, studies in the literature on the effect of salt solutions on hydraulic conductivity are summarized.…”
Section: Salt Solutionsmentioning
confidence: 99%
“…Leachate has different chemical substances that may control its electrical conductivity which subsequently effect the interaction with soil. Study performed by Nayak et al [7]. revealed that the Atterberg limit, compaction and permeability characteristics were modified when 0.5 M NaCl was added to the studied soil in the increments between 0% and 20%.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore understanding the description of a flow regime in field is a tedious task. Further, a compacted clay liner, may react in different ways leading to changes in hydraulic conductivity (Nayak et al 2007, Sunil et al 2009, Nayak et al 2010). Fig.…”
Section: Construction and Hydraulic Conductivitymentioning
confidence: 99%